An investigation on behaviour of 800 MPa grade hot-rolled steels in interrupted ISO 16630 hole expansion testing - Plosila Pekka; Vierelä Raimo; Juntunen Päivi; Kesti Vili; Kömi Jukka; Kaijalainen Antti (MATEC Web of Conferences)
The ISO 16630 hole expansion test is the most widely used method for investigating the stretch-flangeability of steels. However, the limiting hole expansion ratio (HER) does not provide detailed information on the behaviour of the edge during the expansion process. Digital image correlation (DIC) strain measurements allow a more detailed analysis of formability testing. In the standard hole expansion test, accurate imaging of the surface close to the edge is challenging. The aim of this study was to investigate the cut-edge behaviour of high-strength hot-rolled steels with similar tensile strengths at various points in the hole expansion test. Interrupted ISO 16630 tests with punched holes were conducted by discontinuing the tests at different punch strokes. Instead of DIC strain measurement, the specimens were 3D scanned after testing to investigate the thinning of the edge in different sheet directions. Additional tests were performed on specimens with wire electrical discharge machined (W-EDM) holes for comparison. The results showed considerable localisation of edge thinning in the W-EDM specimens, however some localisation was also observed in the punched specimens prior to failure. The deformation along the hole edge is more uniform in the material with the least planar anisotropy.